Atypical fibroxanthoma diagnosed as malignant melanoma - Melato, M... (Acta dermatovenerologica Alpina, Pannonica et Adriatica, 2001)
An atypical fibroxanthoma characterized by aneuploidy and local aggressive behavior was misdiagnosed as malignant melanoma. The reported case contributesto a better understanding of malignant fibro-histiocytic proliferations. A considered evaluation including immunohistochemistry is needed in diagnosing malignant melanoma.
Keywords: Aged; Aneuploidy; Diagnosis, differential; Diagnostic errors; Fibroma; Immunohistochemistry; Melanoma; Xanthomatosis